Reappraisal of Fetal Abdominal Circumference in an Asian Population: Analysis of 50,131 Records - Szu-Ching Lu; Chiung-Hsin Chang; Chen-Hsiang Yu; Lin Kang; Pei-Ying Tsai; Fong-Ming Chang (Elsevier, 2008)
Summary: Objective: Fetuses from different populations may show different growth patterns. In obstetrics, fetal abdominal circumference (AC) is a very useful index for assessing fetal growth. In this study, we attempted to establish the normal fetal growth curves of AC in an Asian population in South Taiwan. Materials and Methods: We reviewed our computer ultrasound database of fetal AC records from January 1991 to December 2006. During the study period of 1 6 years, only the fetuses examined by ultrasonography with gestational age between 1 4 and 41 weeks were included. We excluded extreme bilateral records after initial analysis. Eventually, 50,131 records of AC were included for final analysis. Results: The observed gestation-specific AC values and the predicted AC values were calculated. The best-fit regression equation of AC versus gestational age is a second-order polynomial equation. In general, fetal AC values in our population showed similar patterns to those in Western populations. Besides, we established a table of the predicted AC values based on specific gestational age, including the 5th, 1 0th, 50th, 90th and 95th centiles, for clinical reference. Conclusion: To the best of our knowledge, our series is the largest sample of AC reported in the medical literature. We believe that the gestational age-specific nomogram of fetal AC is important for further clinical assessment of fetal growth. Key Words: abdominal circumference, Asian population, fetus, pregnancy